2020
DOI: 10.1039/d0gc00851f
|View full text |Cite
|
Sign up to set email alerts
|

ElectrochemicalN-demethylation of tropane alkaloids

Abstract: A practical, efficient, and selective electrochemical N-demethylation method of tropane alkaloids to their nortropane derivatives is described. Nortropanes, such as noratropine and norscopolamine, are important intermediates for the semi-synthesis of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…LC-MS analysis of the electrochemical oxidation of 1 a in the divided electrochemical cell clearly showed the presence of 1 b and TEMPOH in the anode compartment, supporting the proposed mechanism (see supporting information, Figure SI 9). Moreover, the formaldehyde produced at the anode upon hydrolysis of the hypothesized iminium intermediate was detected using a derivatization with acetylacetone and ammonia forming 3,5diacetyl-1,4-dihydrolutidine (m/z of 194.1), which was detected by LC-MS. [35,46,47] As expected, there was no formaldehyde detected in the cathode compartment (see supporting information, Figure SI 10).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…LC-MS analysis of the electrochemical oxidation of 1 a in the divided electrochemical cell clearly showed the presence of 1 b and TEMPOH in the anode compartment, supporting the proposed mechanism (see supporting information, Figure SI 9). Moreover, the formaldehyde produced at the anode upon hydrolysis of the hypothesized iminium intermediate was detected using a derivatization with acetylacetone and ammonia forming 3,5diacetyl-1,4-dihydrolutidine (m/z of 194.1), which was detected by LC-MS. [35,46,47] As expected, there was no formaldehyde detected in the cathode compartment (see supporting information, Figure SI 10).…”
Section: Resultssupporting
confidence: 75%
“…Recently, we have successfully applied Shono oxidation for direct electrochemical N-demethylation of tropane alkaloids. [35] However, our effort to directly N-demethylate the important opiate alkaloid 1 a in the same manner or by using a recently reported electrochemical method, [23] under potentiostatic or galvanostatic reaction conditions using either 1 a•HCl or 1 a as free amine, did not lead to the desired N-demethylated compound 1 b. Therefore, we have developed a new indirect electrochemical procedure using TEMPO as electron mediator for the conversion of 1 a to 1 b (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Beside the importance of the N‐dealkylation reaction in the synthesis of drug metabolites, this reaction provides important intermediates for the semi‐synthesis of different medicines [39,40] . For example, N‐dealkylation of atropine to noratropine is an important step for the semi‐synthesis of the bronchodilator ipratropium bromide which is registered in WHO's list of essential medicines [41,42] .…”
Section: Resultsmentioning
confidence: 99%
“…Besides the reported drug metabolism studies, electrochemical N -dealkylation is also applied for the synthesis of pharmaceutical intermediates. We reported that the electrochemical N -demethylation of tropane alkaloids is a selective, facile and scalable approach for the synthesis of nortropane alkaloids ( 56c – 57c , 123c – 125c ) [ 152 ] ( Figure 16 ). As discussed in Section 3.2 , noratropine 56c and noscopolamine 57c are valuable intermediates for the semi-synthesis of 58 and 59 .…”
Section: Electrochemical N -Dealkylationmentioning
confidence: 99%
“…Mechanistic studies supported the formation of an iminium intermediate. The electrochemical N -demethylation of 56a in the presence of cyanide ions (by adding KCN) led to the formation of N -nitrilo noratropine 56d by trapping the iminium intermediate [ 152 ]. Glotz et al [ 153 ] showed that the electrochemical oxidation of opiates with a C14-hydroxyl group, such as 10a , leads to an oxazolidine structure 10c which was also observed for iron and palladium catalytic systems.…”
Section: Electrochemical N -Dealkylationmentioning
confidence: 99%